1998
DOI: 10.1093/molehr/4.12.1099
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between BcI2, Bax and p53: consequences for cell cycle progression and cell death

Abstract: Each cell is under constant surveillance to maintain the integrity of its genome. Genomic lesions in a cell must be repaired before the onset of DNA replication and cell division. In the scenario that the genomic lesion is not repairable, the damaged cells are disposed in an orderly manner known as programmed cell death or apoptosis. Apoptosis and cell cycle progression are two intimately linked phenomena. Uncontrollable cell proliferation perturbs the cellular homeostasis and this can lead to malignancies, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
258
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(279 citation statements)
references
References 93 publications
16
258
0
5
Order By: Relevance
“…The reduction of T may be due to the adverse effect of malathion on the rat hypothalamic- [Korsmeyer, 1999;Basu and Haldar, 1998]. Data from this study clearly indicated the apoptotic effect of malathion by increased expression of Bax and decreased Bcl-2.…”
Section: Discussionmentioning
confidence: 61%
“…The reduction of T may be due to the adverse effect of malathion on the rat hypothalamic- [Korsmeyer, 1999;Basu and Haldar, 1998]. Data from this study clearly indicated the apoptotic effect of malathion by increased expression of Bax and decreased Bcl-2.…”
Section: Discussionmentioning
confidence: 61%
“…18 The process of apoptosis protects the integrity of the genome by eliminating cells with extensive DNA damage or those undergoing uncontrolled proliferation. 11 For instance, during development, RB knockout mice did not experience uncontrolled cellular growth as expected because apoptotic processes eliminated abnormally cycling cells. 21 Similarly, transfection of the G1 cell cycle regulator Cyclin D1 into rat embryo cells, which also disrupts the RB pathway, resulted in increased apoptosis.…”
Section: Discussionmentioning
confidence: 88%
“…6 Bax has been recognized as a potent proapoptotic regulator and the intracellular balance of Bax and Bcl-2 described as a 'rheostat' of apoptosis sensitivity in that the ratio of these proteins influences a cell's ability to respond to apoptotic signals. [11][12][13] Both Bax and Bcl-2 are noted to form homo-and heterodimers and this ratio of these dimeric forms propels the cells towards survival or apoptosis. 11 Two investigators have assessed the expression of BAX and Bcl-2 in in vivo models of castrationinduced prostate apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p53, known as a "guardian of genome", responses to various forms of cytotoxic stress by preventing the proliferation of genetically damaged cells through the control of their cell cycle and/or apoptosis. p53 executes its stress-response programmes through regulation of expression of its target genes, including p21, GADD45α (cell cycle arrest) 4,5 , PUMA 6 , BAX 7 , NOXA 8 , DR5, p53AIP, PIG3, APAF1 (apoptosis) 5 , BTG2, and PaI1(senescence) 5 . In addition to proteincoding genes p53 also controls a number of micro-RNA and long non-coding genes 28: 1739-1751; Grigoreva T et al, Oncotarget, 2015).…”
Section: Introductionmentioning
confidence: 99%